Preparation method of Pi-Pi accumulation-based lithium ion pulse polymer membrane and application of Pi-Pi accumulation-based lithium ion pulse polymer membrane in extraction of lithium from salt lake

By coating polypyrrole onto a carbon nanotube framework and utilizing π-π stacking, the problems of charge accumulation and excessive cross-linking in existing lithium-ion membranes are solved, achieving high selectivity and high adsorption capacity for lithium-ion separation.

CN121060488APending Publication Date: 2025-12-05NORTHEAST DIANLI UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511521933.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-23
Publication Date
2025-12-05

AI Technical Summary

Technical Problem

In existing technologies, the chemical oxidation method for synthesizing polypyrrole can easily lead to charge accumulation and excessive cross-linking, which can damage the conductivity and stability of the membrane and affect lithium ion selectivity and adsorption.

Method used

A lithium-ion imprinted pulsed polymerized film was constructed by coating polypyrrole onto the surface of a carbon nanotube framework using unipolar pulsed electropolymerization technology and combining it with the π-π stacking effect of benzo-12-crown ether-4 to avoid charge accumulation in chemical oxidation methods and site masking caused by traditional crosslinking agents.

Benefits of technology

It improves the membrane's withstand voltage, enhances conductivity and structural stability, improves the high selectivity and adsorption capacity of lithium ions, and maintains structural integrity during long-term cycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121060488A_ABST
    Figure CN121060488A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a pi-pi accumulation-based lithium ion pulse polymer film and application of the polymer film in extraction of lithium from a salt lake, and belongs to the field of ion adsorption. The invention aims to solve the problems that charge accumulation is easily caused when polypyrrole is synthesized by a chemical oxidation method in the prior art, and the selectivity and adsorbability of lithium ions are poor due to excessive cross-linking between a functional monomer and a conductive layer caused by using a cross-linking agent. The method comprises the following steps: 1, preparing an SP-PDA coated PVDF membrane; 2, preparing a CNTs (at) PVDF membrane; 3, preparing a PPy (at) CNTs (at) PVDF membrane; 4, preparing an IIP (at) E-PPCM membrane; the membrane has excellent lithium ion selectivity and high adsorption capacity, by optimizing a polymerization mode and introducing a pi-pi accumulation effect, the withstand voltage of the material is remarkably improved while the high adsorption capacity is maintained, and an efficient and feasible membrane material solution is provided for development of an electrochemical switch ion exchange technology and an ion blotting membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of ion adsorption, specifically relating to a method for preparing a lithium-ion pulsed polymerization film based on π-π stacking and its application in the adsorption of lithium ions. Background Technology

[0002] With the increasing strategic importance of lithium resources, the development of efficient and highly selective lithium-ion separation and recovery technologies is of great significance. Electrochemical switching ion exchange technology, due to its low energy consumption, simple operation, and environmental friendliness, shows broad prospects in fields such as lithium extraction from salt lakes. The core of this technology lies in developing intelligent separation membrane materials that combine excellent ion selectivity and rapid electrochemical response. Polypyrrole (PPy), as a typical conductive polymer, is widely used to construct such functional membranes. However, existing technologies typically employ chemical oxidation to synthesize PPy, which easily leads to localized charge accumulation in the polymer chains, impairing the membrane's conductivity and stability. Furthermore, chemical crosslinking agents are often introduced to immobilize functional monomers, which often results in over-crosslinking problems such as masking of functional sites and obstruction of mass transfer channels. These key scientific issues severely restrict the electrochemical performance and selectivity of lithium-ion imprinted membranes, limiting their practical applications.

[0003] To address this challenge, this study proposes a novel strategy for preparing lithium-ion imprinted pulsed polymerization membranes. This design aims to synergistically enhance the ion adsorption capacity, selectivity, and electrochemical stability of the membrane material, providing a new approach for the development of high-performance lithium-ion separation membranes. Summary of the Invention

[0004] The purpose of this invention is to solve the problems in the prior art where the chemical oxidation method for synthesizing polypyrrole easily leads to charge accumulation, and the use of crosslinking agents causes excessive crosslinking between functional monomers and conductive layers, resulting in poor selectivity and adsorption of lithium ions. The invention provides a method for preparing lithium-ion pulsed polymerization membranes based on π-π stacking and its application in lithium extraction from salt lakes.

[0005] This invention successfully prepared a lithium-ion imprinted pulsed polymerization membrane (IIP@E-PPCM). This membrane utilizes unipolar pulsed electropolymerization technology to coat PPy onto the surface of a carbon nanotube (CNT) framework, effectively avoiding the charge accumulation phenomenon common in chemical oxidative polymerization. To address the issue of over-crosslinking, this invention selects benzo-12-crown ether-4 (B12C4) as the functional monomer, utilizing the π-π stacking interaction between the benzene ring in its structure and PPy to achieve non-covalent self-assembly, thus avoiding the use of traditional crosslinking agents. Furthermore, by combining electrochemically switched ion exchange (ESIX) technology with ion imprinting technology, this membrane exhibits both excellent lithium-ion selectivity and high adsorption capacity. By optimizing the polymerization method and introducing π-π stacking interactions, the withstand voltage of the material is significantly improved while maintaining high adsorption capacity, providing an efficient and feasible membrane material solution for the development of electrochemically switched ion exchange technology and ion-imprinted membranes.

[0006] A method for preparing a lithium-ion pulsed polymerization film based on π-π stacking is carried out according to the following steps:

[0007] I. Preparation of SP-PDA@PVDF membrane:

[0008] ① Mix sodium periodate solution and sodium acetate buffer solution, then add dopamine hydrochloride and stir until homogeneous to obtain a mixed solution;

[0009] ② Place one side of a PVDF membrane in contact with the mixed solution and the other side in contact with air. Shake at a constant temperature for a period of time to obtain a modified PVDF membrane. Turn the membrane over and modify the other side so that the other side is in contact with the mixed solution and the modified side is in contact with air. Shake at a constant temperature for a period of time, wash with water and dry to obtain an SP-PDA@PVDF membrane.

[0010] II. Preparation of CNTs@PVDF membrane:

[0011] Carbon nanotubes and anhydrous methanol were mixed, ultrasonicated, and then ethylene glycol dimethacrylate was added. The SP-PDA@PVDF membrane was then immersed in the mixed solution and heated in a water bath for a period of time under stirring. The membrane was then removed, washed with deionized water, and dried to obtain the CNTs@PVDF membrane.

[0012] III. Preparation of PPy@CNTs@PVDF:

[0013] Using CNTs@PVDF membrane as the negative electrode, Pt as the positive electrode, and saturated KCl solution as the electrolyte, pyrrole was added to the electrolyte. The mixture was cycled multiple times under the following conditions: pulse voltage of 0.8V~0.6V, pulse on-time of 1s~2s, off-voltage of 0V, and pulse off-time of 5s~10s. The membrane was then removed, dried, and PPy@CNTs@PVDF membrane was obtained.

[0014] IV. Preparation of IIP@E-PPCM membrane:

[0015] The PPy@CNTs@PVDF membrane was immersed in a dispersion of benzo-12-crown ether-4, then LiCl was added, and the mixture was ultrasonically stirred magnetically for a period of time. The membrane was then removed, acid-washed, and dried to obtain a lithium-ion pulsed polymerization membrane based on π-π stacking.

[0016] The main principle of this invention:

[0017] This invention employs unipolar pulsed electropolymerization technology to achieve uniform and controllable coating of PPy on the surface of CNTs framework. This method effectively regulates the oxidation-deposition process of pyrrole monomers by adjusting the pulse potential and interval time, promoting the orderly growth of PPy along the CNT surface. This significantly suppresses the local charge accumulation problem caused by continuous oxidation reactions in traditional chemical oxidation methods, improving the uniformity and stability of the conductive network. Regarding the construction of functional sites, B12C4 is selected as the lithium-ion recognition monomer. Utilizing the π-π stacking interaction between its benzene ring structure and the PPy chains, the functional molecules are directionally assembled on a conductive polymer substrate. This non-covalent bonding mode not only avoids the steric hindrance and active site masking problems caused by traditional covalent crosslinking but also enhances the structural stability and electronic conductivity continuity of the composite interface. Pulsed polymerization endows the material with excellent conductivity and high-voltage tolerance, while the π-π stacking interface provides high-density, easily accessible, and specific recognition sites for lithium ions. The synergistic effect of these two processes enables the film to achieve efficient and highly selective capture and release of lithium ions during ESIX technology, while maintaining structural integrity and recognition stability during long-term cycling.

[0018] The beneficial effects of this invention are:

[0019] 1. This invention uses a unipolar pulse electropolymerization method to improve the membrane's withstand voltage, thereby enhancing the membrane's adsorption performance;

[0020] 2. Specific surface area and conductivity of carbon nanotube-enhanced membrane structures;

[0021] 3. Introducing π-π stacking effect to improve membrane selectivity;

[0022] 4. EGDMA crosslinking agent is used to improve the stability of carbon nanotubes loaded onto the membrane. Attached Figure Description

[0023] Figure 1 The curves show the change in lithium ion adsorption capacity of IIP@E-PPCM and IIP@C-PPCM membranes with voltage in ESIX technology;

[0024] Figure 2For IIP@E-PPCM and IIP-E@E-PPCM to Li + Mg 2+ K + Na + The adsorption capacity;

[0025] Figure 3 For IIP@E-PPCM membrane for Li + Stability data graph during multiple adsorption-desorption cycles. Detailed Implementation

[0026] Specific Implementation Method 1: This implementation method is a preparation method of a lithium-ion pulse polymerization film based on π-π stacking, specifically completed according to the following steps:

[0027] I. Preparation of SP-PDA@PVDF membrane:

[0028] ① Mix sodium periodate solution and sodium acetate buffer solution, then add dopamine hydrochloride and stir until homogeneous to obtain a mixed solution;

[0029] ② Place one side of a PVDF membrane in contact with the mixed solution and the other side in contact with air. Shake at a constant temperature for a period of time to obtain a modified PVDF membrane. Turn the membrane over and modify the other side so that the other side is in contact with the mixed solution and the modified side is in contact with air. Shake at a constant temperature for a period of time, wash with water and dry to obtain an SP-PDA@PVDF membrane.

[0030] II. Preparation of CNTs@PVDF membrane:

[0031] Carbon nanotubes and anhydrous methanol were mixed, ultrasonicated, and then ethylene glycol dimethacrylate was added. The SP-PDA@PVDF membrane was then immersed in the mixed solution and heated in a water bath for a period of time under stirring. The membrane was then removed, washed with deionized water, and dried to obtain the CNTs@PVDF membrane.

[0032] III. Preparation of PPy@CNTs@PVDF:

[0033] Using CNTs@PVDF membrane as the negative electrode, Pt as the positive electrode, and saturated KCl solution as the electrolyte, pyrrole was added to the electrolyte. The mixture was cycled multiple times under the following conditions: pulse voltage of 0.8V~0.6V, pulse on-time of 1s~2s, off-voltage of 0V, and pulse off-time of 5s~10s. The membrane was then removed, dried, and PPy@CNTs@PVDF membrane was obtained.

[0034] IV. Preparation of IIP@E-PPCM membrane:

[0035] The PPy@CNTs@PVDF membrane was immersed in a dispersion of benzo-12-crown ether-4, then LiCl was added, and the mixture was ultrasonically stirred magnetically for a period of time. The membrane was then removed, acid-washed, and dried to obtain a lithium-ion pulsed polymerization membrane based on π-π stacking.

[0036] Specific Implementation Method Two: This implementation method differs from Specific Implementation Method One in that: the concentration of the sodium periodate solution mentioned in step one ① is 10 mmol / L to 30 mmol / L; the concentration of the sodium acetate buffer solution mentioned in step one ① is 40 mmol / L to 60 mmol / L; and the volume ratio of the sodium periodate solution to the sodium acetate buffer solution mentioned in step one ① is 1:1. All other steps are the same as in Specific Implementation Method One.

[0037] Specific Implementation Method Three: This implementation method differs from Specific Implementation Method One or Two in that: the mass ratio of dopamine hydrochloride to sodium periodate solution in step one ① is (0.5g~1.5g):50mL; the isothermal oscillation speed in step one ② is 120r•min. -1 ~150r•min -1 The temperature is room temperature, and the time is 1-2 hours; the PVDF membrane mentioned in step 1② has a pore size of 0.45 μm and a diameter of 47 mm. Other steps are the same as in specific implementation method one or two.

[0038] Specific Implementation Method Four: This implementation method differs from Specific Implementation Methods One to Three in that: the carbon nanotubes mentioned in step two are single-walled carbon nanotubes; the mass ratio of the carbon nanotubes to the volume of anhydrous methanol in step two is 0.2 g:(80 mL~100 mL); the mass ratio of the carbon nanotubes to the volume of ethylene glycol dimethacrylate in step two is 0.2 g:(0.1 mL~0.15 mL). The other steps are the same as in Specific Implementation Methods One to Three.

[0039] Specific Implementation Method Five: This implementation method differs from Specific Implementation Methods One to Four in that: the ultrasonic time in step two is 5 to 10 minutes; the stirring speed in step two is 30 r / min. -1 ~50r•min -1 The water bath heating temperature in step two is 60℃~70℃, and the time is 5h~7h. The other steps are the same as in specific embodiments one to four.

[0040] Specific Implementation Method Six: This implementation method differs from Specific Implementation Methods One to Five in that: the number of cycles in step three is 10,000 to 3,000; the volume ratio of electrolyte to pyrrole in step three is (100 to 120):(0.9 to 1). Other steps are the same as in Specific Implementation Methods One to Five.

[0041] Specific Implementation Method Seven: This implementation method differs from Specific Implementation Methods One through Six in that the dispersion of benzo-12-crown ether-4 described in step four is obtained by dissolving benzo-12-crown ether-4 in a mixture of methanol and deionized water, wherein the mass ratio of B12C4 to the volume ratio of methanol to deionized water is 0.1 g: 10 mL: 40 mL. The other steps are the same as in Specific Implementation Methods One through Six.

[0042] Specific Implementation Method Eight: This implementation method differs from Specific Implementation Methods One to Seven in that: the mass ratio of LiCl to the volume ratio of the benzo-12-crown ether-4 dispersion in step four is 0.1 g:(50 mL~100 mL); the sonication time in step four is 5 min~10 min. Other steps are the same as in Specific Implementation Methods One to Seven.

[0043] Specific Implementation Method Nine: This implementation method differs from Specific Implementation Methods One to Eight in that: the magnetic stirring time in step four is 4 to 6 hours; the acid washing method in step four is: immersing the membrane in 1 mol / L HCl for 70 to 80 hours. Other steps are the same as in Specific Implementation Methods One to Eight.

[0044] Specific Implementation Method 10: This implementation method is based on π-π stacked lithium-ion pulsed polymerization membrane for lithium extraction from salt lakes.

[0045] The beneficial effects of the present invention are verified using the following embodiments:

[0046] Example 1: A method for preparing a lithium-ion pulsed polymerization film based on π-π stacking, specifically completed according to the following steps:

[0047] I. Preparation of SP-PDA@PVDF membrane:

[0048] ① Mix 50 mL of 20 mmol / L sodium periodate solution and 50 mL of 50 mmol / L sodium acetate buffer solution, then add 1 g of dopamine hydrochloride and stir well to obtain a mixed solution;

[0049] ② Place one side of a PVDF membrane in contact with the mixed solution and the other side in contact with air, and shake at a constant temperature for 1 hour to obtain a PVDF membrane with one side modified; turn the membrane over and modify the other side, so that the other side is in contact with the mixed solution and the modified side is in contact with air, shake at a constant temperature for 1 hour, wash with water and dry to obtain an SP-PDA@PVDF membrane.

[0050] The isothermal oscillation speed mentioned in step 1② is 150 r•min -1 The temperature is room temperature (25℃).

[0051] The PVDF membrane mentioned in step 1② has a pore size of 0.45μm and a diameter of 47mm;

[0052] II. Preparation of CNTs@PVDF membrane:

[0053] 0.2 g of carbon nanotubes and 50 mL of anhydrous methanol were mixed and sonicated for 5 min. Then, 0.1 mL of ethylene glycol dimethacrylate (EGDMA) was added. The SP-PDA@PVDF membrane was then immersed in the mixed solution and heated in a water bath for 6 h under stirring. The membrane was then removed, washed with deionized water, and dried to obtain the CNTs@PVDF membrane.

[0054] The carbon nanotubes mentioned in step two are single-walled carbon nanotubes;

[0055] The stirring speed mentioned in step two is 30 r / min. -1 ;

[0056] The water bath heating temperature mentioned in step two is 65℃;

[0057] III. Preparation of PPy@CNTs@PVDF:

[0058] Using CNTs@PVDF membrane as the negative electrode, Pt as the positive electrode, and saturated KCl solution as the electrolyte, pyrrole was added to the electrolyte. The membrane was cycled 10,000 times under the following conditions: pulse voltage of 0.8V~0.6V, pulse on-time of 1s~2s, off-voltage of 0V, and pulse off-time of 5s~10s. The membrane was then removed, dried, and PPy@CNTs@PVDF membrane was obtained.

[0059] The volume ratio of electrolyte to pyrrole in step three is 100:1;

[0060] IV. Preparation of IIP@E-PPCM membrane:

[0061] The PPy@CNTs@PVDF membrane was immersed in 50 mL of benzo-12-crown ether-4 dispersion, and then 0.1 g of LiCl was added. The membrane was first sonicated for 5 min and then magnetically stirred for 5 h. The membrane was then removed and immersed in 1 mol / L HCl for 72 h for acid washing and then dried to obtain a lithium-ion pulsed polymerization membrane based on π-π stacking, denoted as IIP@E-PPCM membrane.

[0062] The dispersion of benzo-12-crown ether-4 mentioned in step four is obtained by dissolving benzo-12-crown ether-4 in a mixture of methanol and deionized water, wherein the mass ratio of B12C4 to the volume ratio of methanol to deionized water is 0.1 g: 10 mL: 40 mL.

[0063] The mass ratio of LiCl to the volume ratio of the dispersion of benzo-12-crown ether-4 in step four is 0.1 g: 50 mL.

[0064] Comparative Example 1: This comparative example differs from Example 1 in that, in step four, the PPy@CNTs@PVDF membrane was immersed in 50 mL of benzo-12-crown ether-4 dispersion, then 0.1 g LiCl and 0.1 mL EGDMA (ethylene glycol dimethacrylate) were added. After sonication for 5 min, the temperature was raised to 65 °C, and then magnetically stirred for 5 h. The membrane was then removed and immersed in 1 mol / L HCl for acid washing for 72 h, and dried to obtain the IIP-E@E-PPCM membrane. All other steps and parameters were the same as in Example 1.

[0065] Comparative Example 2: The preparation method of the IIP@C-PPCM membrane is specifically carried out according to the following steps:

[0066] I. Preparation of SP-PDA@PVDF membrane:

[0067] ① Mix 50 mL of 20 mmol / L sodium periodate solution and 50 mL of 50 mmol / L sodium acetate buffer solution, then add 1 g of dopamine hydrochloride and stir well to obtain a mixed solution;

[0068] ② Place one side of a PVDF membrane in contact with the mixed solution and the other side in contact with air, and shake at a constant temperature for 1 hour to obtain a PVDF membrane with one side modified; turn the membrane over and modify the other side, so that the other side is in contact with the mixed solution and the modified side is in contact with air, shake at a constant temperature for 1 hour, wash with water and dry to obtain an SP-PDA@PVDF membrane.

[0069] The isothermal oscillation speed mentioned in step 1② is 150 r•min -1 The temperature is room temperature (25℃).

[0070] The PVDF membrane mentioned in step 1② has a pore size of 0.45μm and a diameter of 47mm;

[0071] II. Preparation of PPy@CNTs;

[0072] 0.2 g CNTs were added to 50 mL of anhydrous ethanol and stirred for 30 min. Then 1 mL of pyrrole was added, and the mixture was sonicated for 5 min. Then 15.15 mL of FeCl3 solution (1 mol / L) was added, and the mixture was reacted for 6 h under ice bath conditions. After washing with 1 mol / L HCl and drying, PPy@CNTs powder was obtained.

[0073] III. B12C4-PPy@CNTs

[0074] 0.5 g of PPy@CNTs powder was placed in a mixed solution of 50 mL of anhydrous ethanol and 50 mL of deionized water, and 50 mL of benzo-12-crown ether-4 dispersion was added. The mixture was sonicated for 1 h, then magnetically stirred for 12 h, allowed to stand for precipitation for 24 h, centrifuged, the supernatant was discarded, and then vacuum dried at 60 °C for 4 h to obtain B12C4-PPy@CNTs powder.

[0075] The dispersion of benzo-12-crown ether-4 mentioned in step four is obtained by dissolving benzo-12-crown ether-4 in a mixture of methanol and deionized water, wherein the mass ratio of B12C4 to the volume ratio of methanol to deionized water is 0.1 g: 10 mL: 40 mL.

[0076] IV. Preparation of IIP@C-PPCM:

[0077] B12C4-PPy@CNTs powder, SP-PDA@PVDF membrane, and 80 mL of anhydrous methanol were mixed and sonicated for 5 min. Then, 0.1 mL of ethylene glycol dimethacrylate (EGDMA) and 0.1 g of LiCl were added, and nitrogen gas was introduced. Subsequently, the water bath temperature was raised to 65 °C, and the mixture was incubated at 50 rpm. -1 The reaction was carried out for 8 hours, the membrane was removed, and excess polymer on the surface was washed with deionized water. The membrane was then acid-washed on a shaker (1 mol of hydrochloric acid) for 24 hours, and then dried at 60°C to obtain IIP@C-PPCM.

[0078] The IIP@E-PPCM membrane prepared in Example 1 and the IIP@C-PPCM membrane prepared in Comparative Example 2 were used as negative electrodes, respectively, and placed in 100 mL of a solution with a concentration of 200 mg / g. -1 In a LiCl solution, a Pt electrode was used as the positive electrode. An electrochemical workstation was employed, with an applied voltage of 0V-1.8V and an adsorption time of 30min. The LiCl content was measured. + The adsorption capacity is shown in the figure. Figure 1 As shown;

[0079] Figure 1 The curves show the change in lithium ion adsorption capacity of IIP@E-PPCM and IIP@C-PPCM membranes with voltage in ESIX technology;

[0080] Figure 1 The results show that the IIP@E-PPCM prepared in Example 1 can rapidly achieve a high adsorption capacity within the operating voltage range of 0V-1.8V. This phenomenon is attributed to the unipolar pulse electropolymerization technology used in this invention. This technology, by controlling the pulse potential and interval time, enables polypyrrole (PPy) to be uniformly coated on the carbon nanotube (CNT) framework, avoiding the charge accumulation problem caused by traditional chemical oxidation methods, thereby forming a continuous and stable conductive network.

[0081] The IIP@E-PPCM membrane prepared in Example 1 and the IIP-E@E-PPCM membrane prepared in Comparative Example 1 were used as negative electrodes, respectively, and 100 mL of each membrane with a concentration of 200 mg / g was added. -1 In LiCl, MgCl2, NaCl, and KCl solutions, with a Pt electrode as the positive electrode, an electrochemical workstation was used. Voltages of 0.3V, 0.6V, 0.9V, 1.2V, 1.5V, or 1.8V were applied, and the adsorption time was 30 min. The Li... + Mg 2+ K + Na + Adsorption capacity.

[0082] Figure 2 For IIP@E-PPCM and IIP-E@E-PPCM to Li + Mg 2+ K + Na + The adsorption capacity;

[0083] From the perspective of selectivity coefficient, IIP@E-PPCM membrane, Figure 2 The results clearly show the effect of the membrane on Li. + It exhibits significantly higher adsorption selectivity, while showing a substantial improvement over IIP-E@E-PPCM in terms of adsorption capacity for other ions. This phenomenon is attributed to the non-covalent fixation of B12C4 onto the PPy substrate through π-π stacking interactions, which avoids site masking caused by EGDMA and thus preserves the highly selective hole structure.

[0084] The IIP@E-PPCM membrane prepared in Example 1 was used as the negative electrode, and 100 mL of a solution with a concentration of 200 mg / g was added. -1 In a LiCl solution, a Pt electrode was used as the positive electrode. An electrochemical workstation was employed with an applied voltage of 1.2 V and an adsorption time of 30 min. The LiCl content was measured. + The adsorption capacity was then determined. The prepared membrane was then used as the positive electrode, placed in 100 mL of deionized water, with a Pt electrode as the negative electrode. An electrochemical workstation was used, with an applied voltage of 1.2 V and an adsorption time of 30 min, to perform Li adsorption. + Desorption. Repeat this cycle 10 times. Figure 3 As shown;

[0085] Figure 3 For IIP@E-PPCM membrane for Li + Stability data graph during multiple adsorption-desorption cycles.

[0086] Figure 3The stability data of the IIP@E-PPCM membrane in multiple adsorption-desorption cycles are presented. For example, after 10 cycles, the lithium-ion adsorption capacity still remains at 88% of the initial capacity. This indicates that the membrane has good cycle durability and structural integrity.

Claims

1. A method for preparing a lithium-ion pulsed polymerization film based on π-π stacking, characterized in that... The preparation method is specifically carried out according to the following steps: I. Preparation of SP-PDA@PVDF membrane: ① Mix sodium periodate solution and sodium acetate buffer solution, then add dopamine hydrochloride and stir until homogeneous to obtain a mixed solution; ② Place one side of a PVDF membrane in contact with the mixed solution and the other side in contact with air. Shake at a constant temperature for a period of time to obtain a modified PVDF membrane. Turn the membrane over and modify the other side so that the other side is in contact with the mixed solution and the modified side is in contact with air. Shake at a constant temperature for a period of time, wash with water and dry to obtain an SP-PDA@PVDF membrane. II. Preparation of CNTs@PVDF membrane: Carbon nanotubes and anhydrous methanol were mixed, ultrasonicated, and then ethylene glycol dimethacrylate was added. The SP-PDA@PVDF membrane was then immersed in the mixed solution and heated in a water bath for a period of time under stirring. The membrane was then removed, washed with deionized water, and dried to obtain the CNTs@PVDF membrane. III. Preparation of PPy@CNTs@PVDF: Using CNTs@PVDF membrane as the negative electrode, Pt as the positive electrode, and saturated KCl solution as the electrolyte, pyrrole was added to the electrolyte. The mixture was cycled multiple times under the following conditions: pulse voltage of 0.8V~0.6V, pulse on-time of 1s~2s, off-voltage of 0V, and pulse off-time of 5s~10s. The membrane was then removed, dried, and PPy@CNTs@PVDF membrane was obtained. IV. Preparation of IIP@E-PPCM membrane: The PPy@CNTs@PVDF membrane was immersed in a dispersion of benzo-12-crown ether-4, then LiCl was added, and the mixture was ultrasonically stirred magnetically for a period of time. The membrane was then removed, acid-washed, and dried to obtain a lithium-ion pulsed polymerization membrane based on π-π stacking.

2. The method for preparing a lithium-ion pulsed polymerization film based on π-π stacking according to claim 1, characterized in that... The concentration of the sodium periodate solution mentioned in step 1① is 10 mmol / L to 30 mmol / L; the concentration of the sodium acetate buffer solution mentioned in step 1① is 40 mmol / L to 60 mmol / L; and the volume ratio of the sodium periodate solution and the sodium acetate buffer solution mentioned in step 1① is 1:

1.

3. The method for preparing a lithium-ion pulsed polymerization film based on π-π stacking according to claim 1, characterized in that... In step 1①, the mass ratio of dopamine hydrochloride to sodium periodate solution is (0.5g~1.5g):50mL; in step 1②, the isothermal oscillation speed is 120r•min. -1 ~150r•min -1 The temperature is room temperature, and the time is 1h~2h; the PVDF membrane mentioned in step 1② has a pore size of 0.45μm and a diameter of 47mm.

4. The method for preparing a lithium-ion pulsed polymerization film based on π-π stacking according to claim 1, characterized in that... The carbon nanotubes mentioned in step two are single-walled carbon nanotubes; the mass ratio of the carbon nanotubes to the volume of anhydrous methanol in step two is 0.2 g: (80 mL ~ 100 mL); the mass ratio of the carbon nanotubes to the volume of ethylene glycol dimethacrylate in step two is 0.2 g: (0.1 mL ~ 0.15 mL).

5. The method for preparing a lithium-ion pulsed polymerization film based on π-π stacking according to claim 1, characterized in that... The ultrasound time in step two is 5 to 10 minutes; the stirring speed in step two is 30 r / min. -1 ~50r•min -1 The water bath heating in step two is at a temperature of 60℃~70℃ for 5h~7h.

6. The method for preparing a lithium-ion pulsed polymerization film based on π-π stacking according to claim 1, characterized in that... The number of cycles in step three is 10,000 to 3,000; the volume ratio of electrolyte to pyrrole in step three is (100 to 120):(0.9 to 1).

7. The method for preparing a lithium-ion pulsed polymerization film based on π-π stacking according to claim 1, characterized in that... The dispersion of benzo-12-crown ether-4 mentioned in step four is obtained by dissolving benzo-12-crown ether-4 in a mixture of methanol and deionized water, wherein the mass ratio of B12C4 to the volume ratio of methanol to deionized water is 0.1 g: 10 mL: 40 mL.

8. The method for preparing a lithium-ion pulsed polymerization film based on π-π stacking according to claim 1, characterized in that... The mass ratio of LiCl to the volume ratio of the benzo-12-crown ether-4 dispersion in step four is 0.1 g:(50 mL~100 mL); the sonication time in step four is 5 min~10 min.

9. The method for preparing a lithium-ion pulsed polymerization film based on π-π stacking according to claim 1, characterized in that... The magnetic stirring time in step four is 4h~6h; the acid washing method in step four is: immersing the membrane in 1mol / L HCl for 70h~80h.

10. The application of the lithium-ion pulse polymerization film based on π-π stacking prepared by the preparation method according to claim 1, characterized in that... Lithium-ion pulsed polymerization membrane based on π-π stacking is used for lithium extraction from salt lakes.